Timing dependent neuronal migration is regulated by Cdk5-mediated phosphorylation of JIP1 - Fei, Qinglin; Im, Doo Soon; Xu, Yiwen; Huang, Tianwen; Qu, Dianbo (Frontiers in Cell and Developmental Biology, 2024)
The mammalian brain, especially the cerebral cortex, has evolved to increase in size and complexity. The proper development of the cerebral cortex requires the coordination of several events, such as differentiation and migration, that are essential for forming a precise six-layered structure. We have previously reported that Cdk5-mediated phosphorylation of JIP1 at T205 modulates axonal out-growth. However, the spatiotemporal expression patterns and functions of these three genes (Cdk5, Cdk5r1 or p35, and Mapk8ip1 or JIP1) in distinct cell types during cortical development remain unclear. In this study, we analyzed single-cell RNA-sequencing (scRNA-seq) data of mouse embryonic cortex and discovered that Cdk5, p35, and JIP1 are dynamically expressed in intermediate progenitors (IPs). Pseudotime analysis revealed that the expression of these three genes was concomitantly upregulated in IPs during neuronal migration and differentiation. By manipulating the expression of JIP1 and phospho-mimetic JIP1 using in utero electroporation, we showed that phosphorylated JIP1 at T205 affected the temporal migration of neurons. Together with our previous findings that phospho-JIP1 at T205 regulates axonal growth, our study uncovers a mechanism by which Cdk5, p35, and JIP1 coordinate to regulate neuronal specification in the developing neo-cortex.